2015
DOI: 10.1007/s11442-016-1266-3
|View full text |Cite
|
Sign up to set email alerts
|

Surface velocity estimations of ice shelves in the northern Antarctic Peninsula derived from MODIS data

Abstract: The ice shelves in the northern Antarctic Peninsula are highly sensitive to variations of temperature and have therefore served as indicators of global warming. In this study, we estimate the velocities of the ice shelves in the northern Antarctic Peninsula using co-registration of optically sensed images and correlation module (COSI-Corr) in the Environment for Visualizing Images (ENVI) based on Moderate Resolution Imaging Spectroradiometer (MODIS) images during 2000-2012, from which we conclude that the ice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…Variance is less than 30 m•a −1 in these two drainages as well, roughly half of the RMSE in comparison between the tie-point pairs and our result. This value of 30 m•a −1 is the same as the velocity retrieval difference between MODIS and Landsat, whose outstanding spectral and georeferencing characteristics have already been recognized [39]. In drainages where moderate scale ice shelves dominate, such as Dronning Maud, Lambert, and Peninsula, the result is yet acceptable since the mean and median of the difference is still relatively low, and the variance of the difference is the same order of that RMSE.…”
Section: Residual In Rock Outcropsupporting
confidence: 54%
See 1 more Smart Citation
“…Variance is less than 30 m•a −1 in these two drainages as well, roughly half of the RMSE in comparison between the tie-point pairs and our result. This value of 30 m•a −1 is the same as the velocity retrieval difference between MODIS and Landsat, whose outstanding spectral and georeferencing characteristics have already been recognized [39]. In drainages where moderate scale ice shelves dominate, such as Dronning Maud, Lambert, and Peninsula, the result is yet acceptable since the mean and median of the difference is still relatively low, and the variance of the difference is the same order of that RMSE.…”
Section: Residual In Rock Outcropsupporting
confidence: 54%
“…Haug et al investigated Larsen-C ice shelf's velocity from 2002 to 2009 via MODIS, and the difference from Landsat's retrieval was within 30 m•a −1 [38]. Coincidentally, the Larsen-C ice shelf was chosen to be the study area again by Chen et al [39], and it was found to have accelerated continually since 2000. In fact, Wang et al [40] and Li et al [41] have exploited Declassified Intelligence Satellite Photography (DISP) images acquired during the Cold War period to trace back to earlier dynamic hints of the Larsen-C ice shelf.…”
Section: Introductionmentioning
confidence: 99%
“…Because the ice flow velocities over stable control points (e.g., mountain peaks, nunataks, or domes) should approach zero, we used the mean ice flow velocities at these control points as the benchmarks for uncertainties resulting from feature-based image matching. This same method has been widely adopted in previous studies [41,42]. Uncertainties resulting from feature-based image matching (i.e., for the mean ice flow velocity at the control points) were approximately 21.26 m/year or within 2 pixels.…”
Section: Ice Flow Velocity Mappingmentioning
confidence: 99%
“…Many studies (e.g. Haug et al, 2010;Chen et al, 2016;Greene et al, 2018) have demonstrated that MODIS data can be successfully used for feature tracking on Antarctic ice shelves.…”
Section: Introductionmentioning
confidence: 99%